Laparoscopic excision of pelvic lymph nodes after vaginal hysterectomy due to histological blunder. Case report of two patients - Pawłowicz, Paweł; Czekańska, Magdalena; Rawski, Wojciech; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2011)
The analysis included two patients who were treated in the First Department of Gynaecology and Obstetrics CMKP in Warsaw. Vaginal hysterectomy was performed because of the diagnosis of atypical endometrial hyperplasia complex. Both studies were performed on an outpatient basis. In the final histological results the endometrial cancers were found: in the first case G2 endometrial cancer, in the second one clarocellulare carcinoma. Patients were re-admitted to the clinic and pre-qualified for the extension of hysterectomies performed with laparoscopic lymphadenectomy of the ilio-obturator area and removal of the parametrium and part of the vagina vault. Patients were submitted for further consultation and treatment at the Cancer Centre.